2019
DOI: 10.1161/jaha.118.011797
|View full text |Cite
|
Sign up to set email alerts
|

Blood Microbiota Modification After Myocardial Infarction Depends Upon Low‐Density Lipoprotein Cholesterol Levels

Abstract: BackgroundThe role of bacteria on the onset of cardiovascular disease has been suggested. Reciprocally, increased intestinal bacterial translocation and bloodstream infection are common comorbidities associated with heart failure and myocardial infarction (MI). In this context, the aim of this study was to analyze the blood microbiome in patients shortly after acute myocardial infarction.Methods and ResultsWe carried out a case control study comparing 103 patients at high cardiovascular risk but free of corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…The study population included ACS patients with available EDTA-plasma sample from the previously described prospective ACS-cohort (FLORINF, NCT02405468) [10]. Cases (n = 99) were patients who experienced an acute ischemic event and included one week after the acute ischemic phase (hereinafter referred to as ACS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study population included ACS patients with available EDTA-plasma sample from the previously described prospective ACS-cohort (FLORINF, NCT02405468) [10]. Cases (n = 99) were patients who experienced an acute ischemic event and included one week after the acute ischemic phase (hereinafter referred to as ACS).…”
Section: Resultsmentioning
confidence: 99%
“…We carried out a case-control study (FLORINF, NCT02405468) recruited in the Cardiology, Arterial Hypertension and Therapeutic department of Toulouse University Hospital Center, France [10]. Cases were patients (n = 99, men and women) who experienced an acute ischemic event and were included one week after the acute ischemic phase.…”
Section: Study Populationmentioning
confidence: 99%
“…In this regard, recent evidence describes the alteration of gut microbiota in established cardiovascular disease [41]. Besides, myocardial infarction has been reported to modulate the blood microbiota, mediated by the increase of intestinal bacterial translocation [42]. Secondly, Haro et al [9] did not address possible differences between OB and MetS, depending on the associated drug treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The blood samples have also higher genus richness and different composition suggesting that the technical contamination had no significant impact. The presence of a specific blood microbiome has already been demonstrated in several diseases such as chronic kidney diseases, liver fibrosis, diabetes mellitus or cardiovascular events (5,14,15).…”
Section: Discussionmentioning
confidence: 99%
“…It has long been thought that blood is a sterile environment. However, recent sequence-based studies have revealed that changes in blood microbiota are associated with various diseases (4,5). Studying blood microbiota is particularly interesting because it is a reflexion of various microbiota (gut, oral, nasal) and it allows thus to determine the presence of bacteria or bacterial DNA that have passed the mucosal barrier.…”
Section: Introductionmentioning
confidence: 99%